An empirical study on the determinants of capital structure of Sarawak-based listed companies / Dayang Rostylawati Awang Ehsan - Awang Ehsan, Dayang Rostylawati (2015)
This chapter serves as the introduction of the study on determinants of capital structure of Sarawak-based listed companies. Essentially, this chapter introduces the study of capital structure and quotes extant literatures to arrive at the basis to determine the variables of this study. This chapter also demonstrates the research objectives of the study. A paragraph is also devoted to the description of the problem statement that leads to the selection of this study. Going forward, this chapter briefly discusses the scope of the study as a more detail write up is put forward in Chapter 3 specially on methodology. This chapter also highlights the significance of this study. Finally, the last section of this chapter discusses the structure and organization of this study.